ENHANCEMENT OF PHOTOCURRENT IN TITANIUM DIOXIDE SEMICONDUCTORS VIA HOT ELECTRON INJECTION FROM SILVER NANOPARTICLES IN WATER SPLITTING SYSTEMS FOR HYDROGEN PRODUCTION - Lukman Andi Priyatna; Yoga Kurniawan; Muhammad Walid Muadab; Hasbullah Hasbullah (Journal of Scientech Research and Development, 2026)
Green hydrogen production through photoelectrochemical (PEC) water splitting is a promising technology for supporting the development of renewable energy. However, the efficiency of PEC systems remains limited due to poor visible light absorption and the high recombination rate of electron–hole pairs in semiconductors such as titanium dioxide (TiO₂). TiO₂ exhibits excellent chemical stability and high electron mobility, but its wide bandgap (~3.2 eV) restricts light absorption mainly to the ultraviolet region, which accounts for less than 5% of the solar spectrum. This study aims to enhance the performance of TiO₂ photoelectrodes through modification with silver nanoparticles by utilizing the localized surface plasmon resonance (LSPR) effect. TiO₂ was synthesized and subsequently decorated with silver nanoparticles using a chemical reduction method followed by a spin-coating technique. Material characterization was carried out using UV–Vis diffuse reflectance spectroscopy (UV–Vis DRS). The PEC performance was evaluated in a three-electrode system using Na₂SO₄ electrolyte under simulated light illumination. The modification with silver nanoparticles is expected to significantly enhance the photocurrent density compared to pristine TiO₂. This study contributes to the development of efficient photoanode materials for solar-driven hydrogen production. By utilizing the localized surface plasmon resonance (LSPR) phenomenon of silver nanoparticles, a significant improvement in photoelectrochemical activity was achieved. Specifically, the deposition of silver nanoparticles on TiO₂ increased the photocurrent density from 0.03 mA cm⁻² to 0.09 mA cm⁻². This enhancement is attributed to improved visible-light absorption induced by the LSPR effect, accompanied by an increase in %ABPE from 0.05% for TiO₂ to 0.1%.